2021
DOI: 10.3390/nano11071835
|View full text |Cite
|
Sign up to set email alerts
|

Surfactants Enhanced Heavy Oil–Solid Separation from Carbonate Asphalt Rocks-Experiment and Molecular Dynamic Simulation

Abstract: In this study, surfactants were used to enhance heavy oil–solid separation, and a detailed mechanism was explored by SARA (saturates, aromatics, resins, asphaltenes) analysis, element analysis, AFM measurement, and molecular dynamic simulation. Surfactants could effectively decrease oil/solid interaction force and then oil–solid separation would be enhanced. The oil–solid interactive force was in relation to surfactants concentration, pH value, asphaltene content, and salinity. The molecular dynamics simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A large amount of research has shown that, in the oil-solid separation process of UHO, both the wettability of the solid surface and the interaction between the heavy oil and the solid play a major role in the oil-solid separation efficiency [42][43][44][45][46]. Therefore, in this section, for the basic theory of oil-solid separation we mainly review the solid wettability, contact angle and oil-solid interaction.…”
Section: Basic Theories Of Oil-solid Separationmentioning
confidence: 99%
“…A large amount of research has shown that, in the oil-solid separation process of UHO, both the wettability of the solid surface and the interaction between the heavy oil and the solid play a major role in the oil-solid separation efficiency [42][43][44][45][46]. Therefore, in this section, for the basic theory of oil-solid separation we mainly review the solid wettability, contact angle and oil-solid interaction.…”
Section: Basic Theories Of Oil-solid Separationmentioning
confidence: 99%
“…Many researchers have utilized molecular dynamics (MD) simulations to study the behavior of commercial surfactants in cEOR. Most of these studies aim to investigate how surfactant molecules interact at the interface, as the success of the cEOR process hinges on the interactions between surface agents and crude oil .…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants were used to enhanced the nanofluids stability. 31 But the detailed mechanism of surfactants effect on the nanofluids heat transfer was unclear. Ma et al 32 affect the Al 2 O 3 -CuO/TiO 2 nanofluids, and the results indicated that the slight of surfactants would enhance the nanofluids heat transfer coefficients, but excess surfactants would decrease the heat transfer coefficients.…”
Section: Introductionmentioning
confidence: 99%